Multiple RNA recognition patterns during microRNA biogenesis in plants - Bologna, Nicolas Gerardo (2013)
MicroRNAs (miRNAs) derive from longer precursors with fold-back structures. While animal miRNA precursors have homogenous structures, plant precursors comprise a collection of fold-backs with variable size and shape. Here, we design an approach to systematically analyze miRNA processing intermediates and characterize the biogenesis of most of the evolutionarily conserved miRNAs present in Arabidopsis thaliana. We found that plant miRNAs are processed by four mechanisms, depending on the sequential direction of the processing machinery and the number of cuts required to release the miRNA. Classification of the precursors according to their processing mechanism revealed specific structural determinants for each group. We found that the complexity of the miRNA processing pathways occurs in both ancient and evolutionarily young sequences and that members of the same family can be processed in different ways. We observed that different structural determinants compete for the processing machinery and that alternative miRNAs can be generated from a single precursor. The results provide an explanation for the structural diversity of miRNA precursors in plants and new insights toward the understanding of the biogenesis of small RNAs.